2001
DOI: 10.1037/0021-9010.86.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Organizational attractiveness of firms in the People's Republic of China: A person–organization fit perspective.

Abstract: The authors investigated factors related to firm attractiveness as an employer in the People's Republic of China. The organizational attributes of type of ownership, nationality of the supervisor, and firm familiarity in organizational descriptions were manipulated and their effects were measured on firm attractiveness. In addition, the authors adopted a person-organization fit perspective to investigate how individual difference characteristics moderated the effects of these organizational attributes on attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
140
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 40 publications
9
140
0
2
Order By: Relevance
“…The antecedent variables include human resource management practices [5][6][7], job and career choices [8,9], performance [10], and socialization tactics [11], whilst the outcome variables include job satisfaction, organizational commitment, organizational citizenship behavior, career success, tenure and turnover rates [5,6,[12][13][14][15][16][17][18][19][20][21]. Although the results of the prior studies generally confirm that better P-O fit leads to enhanced organizational commitment and job satisfaction, as well as lower turnover rates, very little research has been undertaken examining P-O fit as a moderator of the relationship between the study variables [1].…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…The antecedent variables include human resource management practices [5][6][7], job and career choices [8,9], performance [10], and socialization tactics [11], whilst the outcome variables include job satisfaction, organizational commitment, organizational citizenship behavior, career success, tenure and turnover rates [5,6,[12][13][14][15][16][17][18][19][20][21]. Although the results of the prior studies generally confirm that better P-O fit leads to enhanced organizational commitment and job satisfaction, as well as lower turnover rates, very little research has been undertaken examining P-O fit as a moderator of the relationship between the study variables [1].…”
Section: Introductionmentioning
confidence: 68%
“…Hierarchical polynomial regression procedures [1,[40][41][42] were used to determine the extent to which value congruence and the possible moderating effects of professional status were related to the outcome variables. The midpoint of each item was subtracted to centralize the scale in order to alleviate the problems of multi-collinearity associated with curvilinear and interaction terms [43].…”
Section: Analytical Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [22] found that repeated exposure of objects to individuals leads to increased ratings and positive perceptions about them. So, the more a student is acquainted with a company, the more positive will be his/her response to recruiting calls [23] and the higher the attractiveness rate to participate in their selection processes [24]. Therefore, companies should come up with different recruiting strategies to consolidate the memory of their positive attributes in the minds of potential candidates, leading them to apply to the selection processes.…”
Section: Recruiting Undergraduate Students Onlinementioning
confidence: 99%
“…In regard to content dimensions, there are two dominant and distinct frameworks for conceptualizing P-O fit (Cable & DeRue, 2002;Edwards, 2008;Kristof, 1996;Edwards, 1996): (1) The demands-abilities fit; this aspect of P-O fit is also labeled as Person-Job (P-J) fit , which rests on match between abilities and work skills possessed by individual employees and those needed by their organizations (Edwards, 2008;Kristof-Brown et al, 2005); (2) The perspective of needssupplies fulfillment (French, Caplan & Harrison, 1982), another way to conceptualize P-O fit as the extent to which an employee's work preferences or needs get fulfilled by his/her employer (Cable & Edwards, 2004;Locke, 1976;Manhardt, 1972;Meglino, Ravlin & Adkins, 1989;Super, 1970Super, ,1995Wanous & Lawler, 1972). In this study, I will focus on the needs-supplies fulfillment approach of P-O fit for the following reasons: (1) Compared to needs-supplies fulfillment approach, the demands-abilities approach is limited in scope and application in regard to impact on associated outcomes as it is most relevant to the area of recruitment and selection (Turban, Lau, Ngo, Chow & Si, 2001;Edwards & Cooper, 1990;Werbel & Gilliland, 1999); (2) The integration of needssupplies fulfillment approach with Chatman's (1989;1991) value congruence concept described above may afford us with "a more comprehensive picture of fit" (Cable & Edwards, 2004;Kristof, 1996, p. 30). More specifically, drawing the insights from the work-value theory discussed previously, comprehensive comparisons at the individual level can be made across content dimensions associated with work values.…”
Section: Content Of Person-organizational Fitmentioning
confidence: 99%